Improving Energy Efficiency Through Using Modern Hydraulic Oil - Hrobat, Aleš; Mohorko, Jošt; Tič, Vito; Kambič, Milan (International Conference Fluid Power 2025: Conference Proceedings, 2025)
The service life of hydraulic oil is significantly influenced by operating conditions as well as by its composition. Manufacturers have access to different groups of base oils for the production of hydraulic fluids. Due to the varying properties of these groups, the service life of the final product also varies. This article discusses hydraulic oils according to different groups of base oils, their basic characteristics, and the differences between them. Furthermore, it introduces the new series of Energolubric hydraulic oils, focusing on extended service life compared to conventional mineral-based hydraulic oils. Results of comparative testing on oxidation stability of various oils will be presented. The article will also address the aspect of energy efficiency in hydraulic system operation, which is also influenced by the choice of hydraulic oil.